Rezension von: Lidl, Josef; Hahn, Walter, An der Mühlstraße - Gräter, Carlheinz (Württembergisch Franken, 1979)
Josef Lidl und Walter Hahn: An der Mühlstraße. Mit dem Zeichenstift durchs Brombachtal. 117 S., zahlr. Abb. Weißenburg, W. Lühker, 2. Aufl. 1977.